2007
DOI: 10.1016/j.scitotenv.2007.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the applicability of global CFC and SF6 input functions to groundwater dating in the UK

Abstract: Chlorofluorocarbons (CFCs) and sulphur hexafluoride (SF 6 ) are increasingly being used to date recent groundwater components. While these trace gases are generally well-mixed in the atmosphere, there is evidence that local atmospheric excesses (LAEs) exist in some areas of the world, primarily associated with urbanisation and thereby affecting the interpretation of data derived from groundwater studies. Since the soil acts as a low-pass filter for atmospheric trace gas fluctuations, the possible existence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
1
18
1
Order By: Relevance
“…Each of the methods have advantages and drawbacks which can often be site specific, so choosing the best method(s) for a particular site is not straightforward. For example using CFCs in UK lowland catchments in urban settings can be problematic due to point source contamination of the aquifer system with CFCs (Darling and Gooddy, 2007). In most situations a combination of several techniques is required to understand the complex hydrological processes (Cook et al, 2003, Gooddy et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Each of the methods have advantages and drawbacks which can often be site specific, so choosing the best method(s) for a particular site is not straightforward. For example using CFCs in UK lowland catchments in urban settings can be problematic due to point source contamination of the aquifer system with CFCs (Darling and Gooddy, 2007). In most situations a combination of several techniques is required to understand the complex hydrological processes (Cook et al, 2003, Gooddy et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Santella et al (2008) estimate that significant areas of the US, Europe and Asia potentially show elevated SF 6 levels of 10% or more over clean air background. However, studies by Gooddy et al (2006) and Darling and Gooddy (2007) indicate that SF 6 levels close to industrialised urban areas are not always elevated.…”
Section: Local Atmospheric History Of Sfmentioning
confidence: 96%
“…Höhener et al (2002) reported that in 12 of 16 aquifers groundwater was locally contaminated with CFCs in concentrations exceeding equilibrium with respect to modern air. Pathways of CFC input to groundwater such as local atmospheric pollution (Darling and Gooddy, 2007), landfills (Darling et al 2010), and industrial solvent spills (Morris et al, 2006) are widely reported throughout the literature.…”
Section: ; Wagna No 45242)mentioning
confidence: 99%